Hábitos alimentares de trabalhadores em turnos de um frigorífico no sul do Brasil - Freitas, Elisângela da Silva de (Universidade do Vale do Rio dos Sinos, 2012)
OBJECTIVE: The aim of this study was to investigate the relationship between shift work and eating habits of workers in a poultry processing plant in southern Brazil. METHODS: A cross-sectional study was conducted with 1.206 workers, aged between 18 and 50 years, of both sexes. In order to investigate demographic and socioeconomic characteristics, shift work and food habits, standardized questionnaires were administered. Shift work was categorized as day and night shift. The investigation of the dietary habits of the workers was realized through three strategies: (1) research on the number and type of meals taken, (2) timing of meals and (3) building of a food score. RESULTS: The prevalence of risky eating behavior among workers was 33.4% (95% CI 30.69 to 36.09). After adjustment, older, nonwhite women were less likely to present risky eating behavior. With regard to meals, a higher percentage of shift workers reported having 3 or more meals a day. Night shift workers had higher prevalence of consuming afternoon snacks, whereas day shift workers consumed more snacks in the morning and evening. Night and day shift workers also had different timing for meals. CONCLUSION: It was concluded that there is a relationship between demographic characteristics of workers and risky eating behavior, as well as differences in the types of meal according to shift work. The findings suggest the need for specific studies with other workers to better elucidate the characteristics of the eating habits of this population.
Keywords: Saúde dos trabalhadores; Hábitos alimentares; Trabalho em turnos; Occupational health; Food habits; Shift work; ACCNPQ::Ciências da Saúde::Saúde Coletiva